2021
DOI: 10.1039/d0cp05390b
|View full text |Cite
|
Sign up to set email alerts
|

Temperature evolution in IR action spectroscopy experiments with sodium doped water clusters

Abstract: The combination of supersonic expansions with IR action spectroscopy techniques is the basis of many successful approaches to study cluster structure and dynamics. In this paper we elucidate the temperature effect of IR excitation and evaporative cooling on sodium solvation in water clusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
13

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 67 publications
0
7
1
13
Order By: Relevance
“…This is indeed dependent on their temperature. In general, clusters in molecular beams generated by supersonic expansions attain low temperatures, e.g., in extreme 0.37 K for large superfluid He nanodroplets, ∼40 K for large Ar clusters, , 50–180 K for water ice nanoparticles, 90–135 K for methanol clusters, etc. However, the cluster temperature is difficult to determine experimentally, and various models were proposed.…”
mentioning
confidence: 99%
“…This is indeed dependent on their temperature. In general, clusters in molecular beams generated by supersonic expansions attain low temperatures, e.g., in extreme 0.37 K for large superfluid He nanodroplets, ∼40 K for large Ar clusters, , 50–180 K for water ice nanoparticles, 90–135 K for methanol clusters, etc. However, the cluster temperature is difficult to determine experimentally, and various models were proposed.…”
mentioning
confidence: 99%
“…Connected by hydrogen bonds, water molecules assemble large clusters from small clustered structures. Larger water clusters (H 2 O) n have been determined and analyzed by infrared (IR) spectroscopy 14,15 and ab initio calculations. 16 It has been reported that local structures of water are connected to thermodynamic properties to a certain extent.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36][37] In einer anderen und im Rahmen dieser Arbeit erschienenen Publikation wurde aus den genannten Stagnationsbedingungen eine Cluster-Temperatur von etwa 150 K abgeleitet. [115] Bei höherem Druck im Reservoir liegt die Schätzung bei etwa 70 K. [115] Auch die Nachweismethode der Cluster durch IR-induzierte Wirkungsspektroskopie wird in der Studie nochmals beschrieben. Die dabei resultierende Evaporation wird als Teil dieser Arbeit in Unterabschnitt 4.5 erklärt.…”
Section: Wasserunclassified
“…nach Becker et al [28] (Wiederverwendung erfolgt mit Erlaubnis/gemäß den Bestimmungen der PCCP-Eigentümergesellschaften). [28] Carlsson et al 2020 [26] und Becker et al 2021 [115] erschienen. Kinetik wurden IR-spektroskopisch untersucht [24,116] bzw.…”
Section: Dynamische Scans (1 Nm-smps) Und Endverteilungen (Tandem-smps)unclassified
See 1 more Smart Citation